2018
DOI: 10.1016/j.apor.2018.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Fuel savings for a general cargo ship employing retractable bow foils

Abstract: Route simulations were performed on a 100 m long (between perpendiculars) general cargo ship equipped with retractable bow-mounted foils, so-called wavefoils, for resistance reduction and motion damping in waves. Two round-trip routes were simulated: Orkney Islands to Iceland and across the Bay of Biscay. Ship motions and added resistance in waves were calculated in the frequency domain. Foil thrust was calculated in the time domain, based on a frequencydomain model of the vessel motions with wavefoils, using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…Sandvik et al [6] present a simulation-based methodology for investigating ship design susceptibility towards operational delays during marine operations limited by the occurrence of operable weather windows. Bøckmann et al [7] evaluate the fuel saving potential of retractable bow foils by simulating 1000 voyages for two routes in the North Atlantic. In these studies, the understanding of the system's ability to function in its operating environment is evaluated using long-term statistics of system factors.…”
Section: Introductionmentioning
confidence: 99%
“…Sandvik et al [6] present a simulation-based methodology for investigating ship design susceptibility towards operational delays during marine operations limited by the occurrence of operable weather windows. Bøckmann et al [7] evaluate the fuel saving potential of retractable bow foils by simulating 1000 voyages for two routes in the North Atlantic. In these studies, the understanding of the system's ability to function in its operating environment is evaluated using long-term statistics of system factors.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, these devices have gained popularity as secondary propulsion systems. References [5][6][7][8][9][10][11][12][13] provide detailed analysis of the characteristics of such systems. Also, some of the present authors were involved in the research project BIO-PROPSHIP [14] for the investigation of flapping foils.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, an extensive literature review on wave-powered USVs can be found in the aforementioned reference. More recently, Bøckmann et al (2018) estimated the fuel savings for a general cargo ship employing retractable bow foils. They observed that fuel savings were shown to decrease when installed power increases but remain at significant level when the ship advances at full speed.…”
mentioning
confidence: 99%
“…Figure 1.9: The case vessel with wavefoils deployed from work Bøckmann et al (2018) were fuel savings from the wave-foils were estimated. ntua.gr/biopropship), is focused on the hydrodynamic analysis of flapping wings located beneath the ship's hull, operating in random motion; see Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation